Implementation of Problem-Based Learning to Enhance Students Critical Thinking Skills in Junior High School - Sappaile, Baso Intang; Nisak, Sayida Khoiratun; Mustofa, Mustofa; Mendrofa, Netti Kariani; Supendi, Dede (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This qualitative study explores the implementation of Problem-Based Learning (PBL) to enhance critical thinking skills among junior high school students in Indonesia. Recognizing the limitations of traditional teaching methods that emphasize memorization, this research investigates how PBL, which centers on student-driven problem-solving, impacts students"™ analytical abilities, collaboration, and self-directed learning. Data were collected through classroom observations, semi-structured interviews with three teachers and ten students, and analysis of student assignments and reflections over a 12-session period. Thematic analysis revealed that PBL effectively promotes critical thinking by encouraging students to question assumptions, evaluate multiple perspectives, and engage in meaningful dialogue with peers. Additionally, the study found that teachers shifted their roles from information providers to facilitators, which positively influenced student engagement and autonomy. However, challenges such as time constraints, curriculum alignment, and the need for teacher training were identified as barriers to optimal implementation. The findings suggest that with adequate support and adaptation, PBL can serve as a powerful pedagogical approach to develop critical thinking skills in junior high school settings. The study contributes to the growing body of research advocating for innovative instructional strategies in secondary education and offers practical recommendations for educators and policymakers aiming to foster higher-order thinking skills in adolescents.